Analysis of Data Security Algorithms for Grain Storage Systems - Verma, Ankita (My University, 2016)
Large amount of data has been debouched in the coming years therefore data security has become the most important aspect of information sharing. More private data is stored in the cloud. Practically, the quantity of data to be transferred is not the concern. The important factor is the channel, through which the data is transferred, should be secured. Cryptography is one such technique which is can ensure for secure transmission of the data. And, using cryptographic techniques security can be provided to the information. This research work classifies the types of existing encryption algorithms and presents a comparative analysis on Advanced Encryption Algorithm (AES), Data Encryption Standard (DES), and Blowfish algorithm. These algorithms have been implemented on a Grain depot system dataset which consists of granaries and a server from where the expert system accesses the data. This data from the granaries is transferred to the server which is stored in an encrypted form. The algorithms are compared on the basis of different parameters such as throughput value, avalanche effect, perceived performance, performance based on execution time, convergence (convergent algorithms) and power consumption. Code for all the algorithms is written in MATLAB. Throughput value checks if the algorithm is efficient or not, it tells the amount of text encrypted per unit time. Blowfish Algorithm has the high value of throughput nearly 90% increase in the value in comparison to AES and DES. Performance based on execution time checks the speed if the particular algorithm is suitable enough to use. Its value is inversely proportional to the execution time. More is the execution time of an encryption algorithm, less favorable it would be to use. Here also Blowfish Algorithm has outpaced AES and DES algorithm. Perceived performance tells how quickly encryption task is done. It is directly proportional to the real performance of the encryption algorithm. Convergence is checked through the value of cipher text. Blowfish Algorithm produces different value of cipher text whenever it is run, whereas AES and DES produces the same value of cipher text every time it is run. Further, comparison is made on the amount of energy consumed vi by each algorithm. Algorithm which requires low energy and power is favored. Blowfish has nearly 61% decrease in value of power in comparison to AES and DES algorithm. Avalanche effect of an algorithm is calculated by changing a bit in the plain text. After that the value of cipher text is checked. This is again a parameter to check the level of security of an algorithm. Blowfish Algorithm changes the cipher text completely. Hence, it can be concluded that Blowfish algorithm is secure and efficient than the remaining algorithms, therefore it has been used in providing data security to CSIO-CSIR Grain storage data.
ME, CSED
Keywords: Data Security; DES; AES; Blowfish algorithm